2013
DOI: 10.1177/1076029613491459
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Anticoagulant Treatment in Patients With Nonvalvular Atrial Fibrillation

Abstract: The aim of the study was to assess the factors associated with the anticoagulation treatment in patients with atrial fibrillation (AF). A total of 2242 consecutive patients who had been admitted with AF on their electrocardiogram were included in the study. After excluding valvular AF, 1745 patients with nonvalvular AF were analyzed. Mean CHA2DS2-VASc score [cardiac failure, hypertension, age ≥ 75 (doubled), diabetes, stroke (doubled), vascular disease, age 65 -74 and sex category (female)], frequency of persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 21 publications
6
14
0
Order By: Relevance
“…On the other hand, the presence of a vascular disease increased the OAC underuse risk in our study. A similar pattern was reported in an earlier study that showed that heart failure was correlated to an under-average OAC use [34].…”
Section: Causes Of Oac Under-usesupporting
confidence: 88%
See 4 more Smart Citations
“…On the other hand, the presence of a vascular disease increased the OAC underuse risk in our study. A similar pattern was reported in an earlier study that showed that heart failure was correlated to an under-average OAC use [34].…”
Section: Causes Of Oac Under-usesupporting
confidence: 88%
“…This may lead to the decision not to use OAC in AF patients. We also confirm the observation of previous studies that a diagnosis of paroxysmal AF is related to less OAC use [18,34,37]. Whereas guidelines do not differ between types of AF in terms of OAC usage recommendations, treating physicians obviously still see OAC as treatment for patients with more frequent/permanent AF.…”
Section: Causes Of Oac Under-usesupporting
confidence: 88%
See 3 more Smart Citations